CHARACTER EDUCATION MANAGEMENT BASED ON LIVING VALUES EDUCATION (LVE) AT MA AND SMA IN PULANG PISAU CENTRAL KALIMANTAN INDONESIA - Lutfia Anisa; Husnul Yaqin; Suraijiah Suraijiah (Adisam Publisher, 2025)
Schools play a crucial role in character education to create a learning environment that supports moral and ethical values. So character education needs to be implemented in the school environment. Living Values E​ducation (LVE) is an educational approach that is able to meet these needs.This research aims to describe the plan, implement and evaluate character education based on LVE at MA (Islamic Senior High School) and SMA (Senior High School) in Pulang Pisau. This research is field research using a qualitative approach with a case study type of research. The research location are MAN 2 Pulang Pisau and SMAN 1 Pandih Batu. The research subjects were the principal, deputy principal for student affairs, deputy principal for curriculum, religious education teacher, citizenship education teacher, guidance and counseling teacher, and administrative staff. The object of this research is character education management based on LVE at MA and SMA in Pulang Pisau. The data collection techniques are carried out by observation, interviews and documentation. The results of the research show: (1) Planning for character education based on LVE in MA and SMA in Pulang Pisau Regency, namely identifying the values ​​that want to be implemented; identify strategies to be used, and identify obstacles; (2) Implementation is carried out through several school activities, including classroom learning, habituation, extracurricular activities, collaboration between parents and the community, Pancasila Student Profile Strengthening Project activities (P5), as well as through guidance and counseling services; (3) Evaluation carried out once a month, at the end of the semester and at the end of the year by referring to written reports, submissions from teachers/coaches and based on the results of observations and observations of the school principal. The aspects evaluated include aspects of the implementation of activities and aspects of the development of students' conditions at school.